Legal Vacuum in Deferred Prosecution Agreements and Its Implications for Law Enforcement Disparity in Indonesia - Nafirah, Siti Adinda; Nanda Yuniza Eviani (JUSTISI, 2026)
This study aims to analyze various normative and procedural weaknesses within the framework of Deferred Prosecution Agreements (DPAs) in Indonesia, particularly regarding the lack of established sentencing guidelines and proportionality parameters, the lack of clarity regarding methods for calculating state financial losses, limited transparency, and inadequate procedural safeguards. This study employs a normative legal research methodology with a qualitative approach, utilizing a statutory approach, a conceptual approach, and a comparative approach. The study focuses on relevant legislation, doctrinal constructs, and institutional designs related to the regulation of DPA in Indonesia. Additionally, this research compares regulatory frameworks in the United States, the United Kingdom, and Singapore to identify governance models and procedural safeguards that can be applied in negotiation-based corporate law enforcement. The novelty of this research lies in the analysis of DPAs, which is not only situated within the context of prosecutorial discretion but also in relation to the corporate insolvency regime, including bankruptcy and debt repayment deferral (PKPU). The results of the research indicate that DPA regulations in Indonesia have not yet been established through an adequate framework. These issues are evident in the absence of sentencing benchmarks and proportionality, the lack of uniformity in methods for assessing state losses, low transparency, and the fragility of procedural accountability. This situation creates room for unfocused prosecutorial discretion, inconsistent application of the law, and potential disparities in the outcomes of negotiated justice. The conclusion of this study is that the implementation of DPAs in Indonesia requires an integrated governance framework, emphasizing structured discretion, clear measures of proportionality, judicial oversight, transparency, and interagency coordination. Strengthening these aspects is necessary to ensure legal certainty, maintain public trust, and uphold the legitimacy of negotiated justice in the enforcement of corporate criminal law.